2015
DOI: 10.1136/annrheumdis-2015-207601
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in ANCA-associated vasculitis: a meta-analysis

Abstract: This meta-analysis identified 33 genetic variants associated with AAV, supporting a role for alpha-1-antitrypsin, the major histocompatibility complex system, and several distinct inflammatory processes in AAV pathogenesis. Our results indicate that subdivision of AAV based on ANCA serotype has a stronger genetic basis than subdivision based on clinical diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 44 publications
4
59
0
4
Order By: Relevance
“…This was also highlighted in a recent meta-analysis that showed some of these genes, but also for example HLA and SERPINA1 as described above, to be associated with AAV. This study also confirmed that subdivision of AAV by ANCA serotype rather than clinical phenotype has stronger genetic basis (Rahmattulla et al 2016). …”
Section: Genetic Risk Factorssupporting
confidence: 73%
See 1 more Smart Citation
“…This was also highlighted in a recent meta-analysis that showed some of these genes, but also for example HLA and SERPINA1 as described above, to be associated with AAV. This study also confirmed that subdivision of AAV by ANCA serotype rather than clinical phenotype has stronger genetic basis (Rahmattulla et al 2016). …”
Section: Genetic Risk Factorssupporting
confidence: 73%
“…PR3 released by activated neutrophils promotes formation of bradykinin and thereof increased vasopermeability and inflammation (Kahn et al 2009). This can be inhibited by the PR3 inhibitor α1-antitrypsin, but the genetic variations of this gene in AAV patients (Rahmattulla et al 2016) could possibly disrupt this regulation.…”
Section: Neutrophil Recruitmentmentioning
confidence: 99%
“…In addition, the eQTL risk allele was correlated with upregulation of FCGR2A in lymphoblastoid cells. This genetic locus has previously been associated with a genome-wide significance in Kawasaki disease [52], and modest significance in giant cell arteritis [53] and ANCA-associated vasculitis [54]. FCGR2A has an important role in humoral immunity, and it is expressed on most leukocytes and can bind immune complexes to initiate antibody-dependent cellular cytotoxicity and the release of pro-inflammatory mediators [55].…”
Section: Complement-binding Genesmentioning
confidence: 99%
“…The authors found that in 76% of the genetic variants, a subdivision based on ANCA serotype resulted in higher odds ratios than a subdivision based on clinical diagnosis. The results indicated that a subdivision of AAV based on ANCA serotype has a stronger genetic basis than a subdivision based on clinical diagnosis [30]. It is important to note that GWAS identify specific DNA locations, not complete genes.…”
Section: The Complement System In Human Aavmentioning
confidence: 99%
“…The study also investigated whether diagnostic and serological subtypes within AAV have distinct genetic backgrounds [30]. The authors identified 33 genetic variants associated with AAV.…”
Section: The Complement System In Human Aavmentioning
confidence: 99%